2019
DOI: 10.1051/0004-6361/201936348
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology of evolved stars to constrain the internal transport of angular momentum

Abstract: Context. Asteroseismic observations enable the characterisation of the internal rotation of evolved stars. These measurements reveal that an unknown efficient angular momentum (AM) transport mechanism is needed for subgiant and red giant stars in addition to hydrodynamic transport processes. A revised prescription for AM transport by the magnetic Tayler instability has been recently proposed as a possible candidate for such a missing mechanism. Aims. We compare the rotational properties predicted by this magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 32 publications
5
79
0
Order By: Relevance
“…The second subgiant, KIC8524425, is less constraining because it has a higher value of log g, and so even relatively low values of α can produce near solid-body rotation for this star. This is consistent with the value inferred by Eggenberger et al (2019b) for the least evolved stars of D14, but yields a too low degree of differential rotation to account for the most evolved ones of the sample.…”
Section: Comparison With Predictions From Potential Am Transport Mechsupporting
confidence: 90%
See 1 more Smart Citation
“…The second subgiant, KIC8524425, is less constraining because it has a higher value of log g, and so even relatively low values of α can produce near solid-body rotation for this star. This is consistent with the value inferred by Eggenberger et al (2019b) for the least evolved stars of D14, but yields a too low degree of differential rotation to account for the most evolved ones of the sample.…”
Section: Comparison With Predictions From Potential Am Transport Mechsupporting
confidence: 90%
“…So far, their impact on the rotation evolution of subgiants and red giants has been addressed only under the debated assumption of the Tayler-Spruit dynamo in radiative interi-ors (Spruit 2002), and its revision based on a different saturation process by Fuller et al (2019). Comparisons with asteroseismic measurements have shown that this process is currently unable to correctly account for the internal rotation of subgiants and red giants (Cantiello et al 2014, den Hartogh et al 2019, Eggenberger et al 2019b, den Hartogh et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of magnetohydrodynamical (MHD) instabilities could lead to a turbulent transport which would efficiently redistribute the angular momentum. This possibility has been studied recently (Cantiello et al 2014;Fuller et al 2019;Eggenberger et al 2019) with the conclusions unclear so far.…”
Section: Introductionmentioning
confidence: 99%
“…We investigate whether this formalism can lead to core rotation rates that match the observational range of rotation rates during the core He burning phase and the DAV temperature range. Our findings are: -When including the Fuller-formalism in our stellar models, we need an α value of at least 2 to reach the core rotation rates of the intermediate stars analysed by Deheuvels et al (2015), while lower values are needed to match core rotation rates of low mass star (Eggenberger et al 2019b); -After continuing with these stellar models with α = 2−4 to the white dwarf phase, we found that the resulting white dwarf rotational periods are in the range of 81-280 h;…”
Section: Discussionmentioning
confidence: 97%
“…These tests, which have only concerned low-mass stars, show that the Fuller-formalism in its current form is not the full solution to the missing process of AM transport. In particular, Eggenberger et al (2019b) shows that the Fuller-formalism has trouble reproducing the core rotation rates of subgiant stars and argues that different values of free parameter α are needed to match consecutive stellar evolutionary phases.…”
Section: Introductionmentioning
confidence: 99%